2003
DOI: 10.1093/intqhc/mzg057
|View full text |Cite
|
Sign up to set email alerts
|

Reducing clinical variations with clinical pathways: do pathways work?

Abstract: The overall purpose of clinical pathways is to improve outcome by providing a mechanism to coordinate care and to reduce fragmentation, and ultimately cost. Our results demonstrated that it is possible to achieve this goal. Although controversial elements still exist, we think that clinical pathways can have a positive impact on quality in health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
282
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(290 citation statements)
references
References 30 publications
6
282
0
2
Order By: Relevance
“…Implementation of routine distress screening programs in Canada and the US provides practical guidance for successful implementation [9,10,32] as the barriers and facilitators identified were similar to those identified in our pilot research [23]. Recommendations related to active engagement with local teams and identification of local champions [16,33 ] have informed our approach to local implementation. An educational outreach program, an important component of change management within healthcare [34], is also currently being piloted.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Implementation of routine distress screening programs in Canada and the US provides practical guidance for successful implementation [9,10,32] as the barriers and facilitators identified were similar to those identified in our pilot research [23]. Recommendations related to active engagement with local teams and identification of local champions [16,33 ] have informed our approach to local implementation. An educational outreach program, an important component of change management within healthcare [34], is also currently being piloted.…”
Section: Discussionmentioning
confidence: 63%
“…Our results confirmed multidisciplinary support for routine formal screening of anxiety/depression in oncology, combined with a stepped-care model of treatment and review. A key factor in the successful translation of pathways into practice is ownership by all health professionals during the development phase [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In health care the professional autonomy of clinicians creates a barrier to the implementation of standardised clinical pathways. 11 We believe that variance analysis can assist in addressing the difficulties experienced in introducing standardised care by enabling clinicians to implement an objective measure to review practice. Additionally, with the ageing population in Australia, patients tend to present with more comorbidities 12 and treatment plans need to be flexible enough to accommodate specific patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, including six RCTs [4,7,38,51,63,71], failed to show any positive effects on quality associated with practice guidelines [5,10,20,25,26,36]. Results were mixed in 12 studies, in which practice guidelines improved quality for certain outcomes or patient subgroups but not others [8,23,24,41,43,52,54,55,58,59,73,74]. Finally, three systematic reviews reported that clinical practice guidelines could improve the efficacy, efficiency, and cost-effectiveness of care; however, the size of effect was variable and generally small [6,27,47].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%